Evolução dos inventários nacionais de gases de efeito estufa para o setor de uso da terra, mudança de uso da terra e florestas - Laura Virgínia Soares Veloso (2019)
Brazil ratified the Convention, it has submitted three national GHG inventories: the first communication in 2004, the second in 2010 and the third in 2016. In these documents, the contribution of the Land Use, Land Use Change and Forestry (LULUCF) in total emissions. Therefore, this being key sector, the main objective of this study was to understand the evolution of LULUCF sector emissions accounting methodologies in Brazil's GHG inventories, as well as to analyse comparatively the origins and implications of methodological changes between the Second and Third Inventory in accounting for emissions for 2005. This year's review is particularly important because the country's nationally determined contribution (NDC) was calculated on a 2005 basis, and the Third Inventory has a total net emission 25% higher than the same reporting year for the Second Inventory. Since there is still a debate, both within the country and at the UNFCCC, on how methodological changes in communications should be reflected in climate goals, a better understanding on this topic could contribute to the implementation of the Paris Agreement in Brazil and in other countries with similar challenges. The analysis showed that, historically, Brazil dedicates a great effort to improve the methodology of the LULUCF sector estimates. This improvement is responsible for the differences in 2005 emissions produced by the Second and Third Inventories. The results indicate that these two documents are distinguished in two main aspects: deforested areas, and removal factors. In the Amazon, a biome that accounts for most emissions from the sector, the Third Inventory observed a deforested area 51% higher than in the previous Inventory, while there was a reduction in 31% of the removal potential from primary forests. It is expected that the continuous improvement of the estimates will be maintained by Brazil, since many changes are already planned for the Fourth Inventory. It is recommended that in the next Inventories Brazil include emissions from fires not associated with deforestation and hydroelectric dams, as well as the monitoring of activities related to key mitigation policies (e.g. CO2 removals from agricultural soils, proposed in Plano ABC and the NDC). In addition, there should be better coordination between national initiatives and other environmental institutions in order to continue improving the GHG reporting of LULUCF sector. Lastly, considering the strategic and public policy nature of this instrument, it is important that the Inventory methodology reflect not only the best available science, but also be aligned with the conduct of other countries.